Sistem Pengolahan Air Limbah Pada Pembangkit Listrik Tenaga Uap (PLTU) : Studi Kasus PLTU Muara Karang - Sahlan Sahlan; Abdul Razak (JURNAL POWERPLANT, 2013)
Center Steam Power (power plant) is a system of several generating units that rely on mechanical energy from the steam to generate electricity. One type of waste generated by the activities of Steam Power (power plant) is a liquid waste. Power Plant is one of the Thermal Power Plant which contributes removable waste water into the surrounding environment. Waste water originating from a variety of operational activities in the area of ​​the power plant when released into the environment without prior treatment can harm organisms that live around and through the food chain can also be harmful to human health because it generally contains a substance or substances that are potentially harmful. Based on this, the facility power plant waste water treatment system is a very important part of the system of Thermal Power Plant. This research was conducted at the facility Wastewater Treatment System / Waste Water Treatment Plant (WWTP) Muara Karang power plant. The research aims to study the WWTP plant process including the technology and materials used in processing and also compare the data output / results of initial processed WWTP design (2003) with the actual (2011). The results are expected to be used to determine the extent of conformity between the levels of contaminants are released into the environment with the quality standards recommended by the Government. The method used in this research is the field surveys and interviews, as well as data analysis by descriptive analytic. The results showed that the output of the WWTP plant Muara Karang meet quality standards, ie BOD5 3 mg / l, Chromium total 0 mg / l, Copper 0.05 mg / l, Iron 0.16 mg / l, Zinc 0.16 mg / l , pH 7.32, Oils and Fats 0.668 mg / l. Efficiency of processed products for the Iron is 87.2%, Zinc 46.67%, 21.41% Oils and Fats. Based on these data it can be seen that the process of wastewater treatment systems Muara Karang power plant includes five stages, namely the pretreatment, primary treatment, secondary treatment, tertiary treatment and sludge treatment. The performance of several components of the WWTP is less efficient due to have a lot of damage. Quality of output / processed WWTP Muara Karang power plant still operates properly, meet the quality standard of waste water issued by the government and safe for discharge into water bodies / sea.